ANALYZING THE GRAMMATICAL FEATURES OF ADJECTIVES. THE ADJECTIVE AS A WORD EXPRESSING QUALITY OF A SUBSTANCE. QUALITATIVE AND RELATIVE ADJECTIVES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article delves into the grammatical features of adjectives and explores their role as words expressing the quality of a substance. Adjectives, as a fundamental part of language, play a crucial role in providing descriptive details and enhancing communication. This study specifically focuses on two primary categories of adjectives: qualitative and relative adjectives.